Treatment of chronic hepatitis C virus infection in Rwanda with ledipasvir–sofosbuvir (SHARED): a single-arm trial. (February 2019) - Gupta, Neil; Mbituyumuremyi, Aimable; Kabahizi, Jules; Ntaganda, Fabien; Muvunyi, Claude Mambo; Shumbusho, Fabienne; Musabeyezu, Emmanuel; Mukabatsinda, Constance; Ntirenganya, Cyprien; Van Nuil, Jennifer Ilo; Kateera, Fredrick; Camus, Gregory; et al.
Summary: Background: Limited treatment data are available for hepatitis C virus (HCV) in sub-Saharan Africa, especially for genotype 4. Our objective was to establish the safety and efficacy of ledipasvir–sofosbuvir for chronic HCV genotype 1 or 4 infection in adults in Rwanda. Methods: We did a single-arm trial to evaluate the safety and efficacy of ledipasvir–sofosbuvir in Rwandan adults with chronic HCV infection at a single study site (Rwanda Military Hospital, Kigali, Rwanda). We enrolled individuals aged 18 years or older with HCV genotype 1 or 4 infection and a plasma HCV RNA concentration of more than 1000 IU/mL at screening. All participants were given ledipasvir (90 mg) and sofosbuvir (400 mg) in a single combination tablet once daily for 12 weeks. We established HCV genotype using an Abbott platform, and HCV subtype with PCR amplification. The primary endpoint was the proportion of participants with a sustained virological response 12 weeks after therapy (SVR12). All patients enrolled in the study were included in the primary endpoint analyses. This study is registered withClinicalTrials.gov, numberNCT02964091 . Findings: 300 participants were enrolled between Feb 6, 2017, and Sept 18, 2017, and the follow-up period was completed on March 1, 2018. On genotyping, 248 (83%) participants were reported as having genotype 4, four (1%) genotype 1, and 48 (16%) both genotype 1 and genotype 4. Subsequent viral sequencing showed all participants actually had genotype 4 infection with subtype 4k (134 [45%]), subtype 4r (48 [16%]), subtype 4q (42 [14%]), and subtype 4v (24 [8%]) predominating. Overall, 261 (87%, 95% CI 83–91) participants achieved SVR12. In participants with genotype 4r, SVR12 was observed in 27 (56%, 95% CI 41–71) participants versus 234 (93%, 90–96) individuals with other subtypes. There were no drug-related treatment discontinuations due to ledipasvir–sofosbuvir. The most common adverse events were hypertension (97 [32%]), headache (78 [26%]), dizziness (61 [20%]), and fatigue (56 [19%]). There were six serious adverse events; none were assessed to be due to the study drug. 296 participants had data for pill counts at week 4 and 8; 271 (92%) had 100% adherence and only one (<1%) had an adherence of less than 90%. Interpretation: This is the first large-scale prospective study reporting direct-acting antiviral outcomes in sub-Saharan Africa. The high adherence and treatment success without intensive support measures or highly specialised clinical providers, and lack of treatment discontinuations due to adverse events support the feasibility of HCV treatment decentralisation and scale-up in sub-Saharan Africa. Genotype 4r is uniquely expressed in this region and associated with high rates of treatment failure, suggesting a need for rigorous test-of-cure in clinical practice and consideration of the use of newer pangenotypic direct-acting antiviral regimens in this region. Funding: Gilead Sciences.